Dual contraceptives and associated predictors in HIV positive women: a case-control study - Alemu Ashore; Desta Erkalo; Ravi Prakash (BMC, 2022)
Plain language summary HIV/AIDS has become a serious global threat to human beings. People living with HIV are an important group that needs attention. About 90% of the children get HIV infection through their mothers that involved mother-to-child transmission of HIV. Therefore, World Health Organization has focused on the use of condoms to prevent the transmission of sexually transmitted diseases (STDs) and to avoid unwanted pregnancies. Out of these contraceptives, the use of dual contraceptives has been considered the best to prevent the transmission of STDs/HIV. Therefore, the present study tried to identify the use of dual contraceptives (barrier condoms i.e., male, and female condoms) and factors associated with its use in sexually active HIV women in Hossana, SNNPR, Ethiopia. We conducted a case-control study and recruited 312 sexually active HIV positive women that were on antiretroviral therapy and visiting the ART clinics for their follow-ups. The present investigation revealed that women living in rural areas were not aware about the use of dual contraceptives when compared to urban areas. Also, it was observed that women, those involved in sexual activities with multiple partners and had an open discussion with their partners about using dual contraceptives at first were more when compared to others. Although, the use of dual contraceptives among HIV positive women living in Hossana was low. Hence, this needs more focused awareness programs in rural areas and people having sexual intercourse with regular partners.